Self-care activities among patients with diabetes attending a tertiary care hospital in Biratnagar, Nepal (Journal of Nobel Medical College, 2018)
Background: Diabetes mellitus is a complex disease and has emerged the worldwide. Self care management is very important to control and prevent from complications. Although it can be preventable by adopting the healthy numerous skills and health education. Method and Materials: A cross-sectional study of 141 patients with >1-year duration of type 2 diabetes mellitus (DM) were interviewed at Nobel Medical College Teaching Hospital using a non-probability sampling technique to select the sample between October 2017 -January 2018 to respond the diabetic self care questionnaire. For the analysis the descriptive statistics was used. T test and anova were used for the association between the variables. Result: A total of 141 diabetic were participated in the study, in which 50.4% were male and 49.6% female. Among the respondents 27% were in the age group below 50 years, 50.4% were illiterate, 42.6 % were overweight and most of the respondents had duration of disease between 1 to 5 years. The mostly performed self care activities were foot care whereas least was blood sugar monitoring. The mean score of self care behavior of respondents was 53.56 ± 4.48. Among them 50.4% of respondents had self care behavior below 69.5% i.e. had poor practice and 78% scored 69.5% and above 49.6% i.e. had good practice. The obtained results showed that there is significant association of self care behavior with age, education level, occupation and age at diagnosis but not with sex.Conclusion: The scenario of self care activities in some areas were found not up to the mark. So health personnel should provide education to the people with diabetes as it has significant benefit with regard to have better quality of life and prevention of complications.Journal of Nobel Medical CollegeVolume 7, Number 1, Issue 12, January-June 2018, Page: 11-17